A delegacia dos fundos : uma etnografia na delegacia especializada de atendimento à mulher - Silva, Rosa Maria Frugoli da [UNIFESP] (2017)
Violence against women is a complex problem and its consequences are manifested on the health and wellbeing of the women, bringing issues to coping in politics. Among the services of special attendance in this case, the Delegacia Especializada de Atendimento à Mulher (DEAM) has prominent position. Besides registration of occurrences, investigations and repressions of conduct based on the gender of configured crimes and criminal offenses, this should emphasize the reception by active listening and having a professional qualifying team towards the law 11.340/06. This qualitative study aimed to analyse the reality of a DEAM, with women suffering violent situations, and the police officers who work at the station. It consisted of an ethnography of a DEAM in the interior of São Paulo state, revealing a field of affections and interactions that showed the Station’s particularities in ways that influence people’s lives, even though they are not visible in police records. The relationships between the station’s police officers and the population revealed that these women are opposed to violence, though their relationships are sometimes antagonistic. Women victims of violence and police officers must necessarily rely on necessarily different vocabularies; while police approached women’s narratives of crimes according to precepts of law and justice, victims want public safety and health. Violence was relational, involving vocabularies of familiar relationships and interfering in women’s everyday lives, but it also appeared here as a registry, a right, or an action to be taken. This ethnography showed the DEAM’s limits, tracing the Station’s difficulties in attending to women’s needs. The DEAM revealed the anguish of individual voices, but it also emerged as a locus for conflict resolution and for negotiations beyond the logic of criminal justice; it is a space in which women speak about themselves and their experiences, and that can effectively shelter them as they claim their rights.